2018
DOI: 10.2337/dc18-0351
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Predicting Longitudinal Change in Type 1 Diabetes Management During the Transition to Emerging Adulthood

Abstract: Abilities involved in performance on EF tests may be one resource for maintaining better glycemic control during the transition to emerging adulthood. Assessment of such EF abilities may allow for the identification of individuals who are most at risk for deterioration of glycemic control during this transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…We based our power analysis on prior work detecting change in SR targets [4] and T1D medication adherence literature [10,11]. We anticipate medium effect sizes of 0.6 with the bundled interventions, so our proposed sample size of 94 (47 per group) should result in sufficient statistical Power of 82% to detect such effects using a two-sided Type I error alpha of 0.05.…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation
“…We based our power analysis on prior work detecting change in SR targets [4] and T1D medication adherence literature [10,11]. We anticipate medium effect sizes of 0.6 with the bundled interventions, so our proposed sample size of 94 (47 per group) should result in sufficient statistical Power of 82% to detect such effects using a two-sided Type I error alpha of 0.05.…”
Section: Powermentioning
confidence: 99%
“…SR capacity has been conceptualized as including three component processes: executive functioning skills; emotion regulation strategies; and ability to delay gratification in service of achieving future goals [3,4]. Low SR capacity has been shown to interfere with individuals' engagement in a variety of health maintenance behaviors including engaging in regular physical activity [5], consuming a healthy diet [6][7][8], and adhering to medical treatment regimens [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other individuals may become demotivated by having higher HbA 1c values, shifting their attention away from a healthy diet and adaptive eating patterns. Executive function may also be an important variable in this respect, as lower executive function has been related to higher HbA 1c values and DEB in youth with type 1 diabetes (35,36). Hence, future research should examine this codevelopment of DEB and glycemic control, with a specific focus on reciprocal pathways and mechanisms, paying attention not only to the psychological but also the physiological level (e.g., disrupted hunger and satiety sensations due to glycemic dysregulation) (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…In this study no association was found between the trajectories of self-reported adherence and cognition. Emerging adults' reports of adherence did not vary greatly across the 3 years (see also Berg et al, 2018), likely making it difficult to predict the small changes that did occur. Additionally, emerging adults' self-reports of adherence are only modestly related to other metrics of adherence such as blood glucose checks (Berg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, after teens graduated from high school and became more independent, changes in their HbA1c values were predicted by EF performance beyond IQ. Specifically, we found that (a) the teens' ability to make adaptive behavioral choices predicted, beyond IQ, changes in HbA1c from baseline to one-year follow-up (Suchy et al, 2017), and (b) the teen's performance on an EF composite comprised of both cognitive and behavioral components predicted, beyond IQ, changes in HbA1c (though, surprisingly, not changes in self-reported adherence) two years later (Berg et al, 2018).…”
mentioning
confidence: 80%